Design and development of ADS-B receiver - Saw Eh Tha Khu (2019)
The rapid boom in the number of passengers for air travel has increased the demand for the number of flights at a very fast pace. As stated by International Air Transport Association (IATA), the estimated number of passengers may rise to 7.3 billion by 2034 [1]. One of the main challenges that arise is the increase in air traffic density, particularly at the airport area [2]. Thus, techniques such as minimizing the separation between aircrafts became necessary to ensure efficient and fast taxi, landing and take-off of the aircrafts to avoid delays. This has resulted in the need for a more efficient and precise air navigation applications to accommodate the rise in the number of flights. Automatic Dependent Surveillance Broadcast (ADS-B) is one potential solution for the abovementioned issue. ADS-B is a technology where the identity, position and various other information of an aircraft is determined via satellite technology. The ADS-B signals are regularly transmitted by the transponders on the aircraft and these signals are able to be received by any air traffic control ground station as well as other aircrafts equipped with proper ADSB receiver. This provides the opportunity to create an environment with shared information, which improves situation awareness to identify and eliminate potential hazards efficiently [3]. Furthermore, aircrafts equipped with ADS-B system provides air traffic control with aircraft information by emitting ADS-B signal at 1 second intervals as compared to current radar technology which requires 5 to 12 seconds. Thus, ADS-B has better accuracy compared to the traditional primary and secondary radar [4].However, ADS B system is still in its early stage with a lot of room for improvements. Firstly, ADS-B system is not secured and can be hacked easily [6]. Although the ADSB data broadcast is open and useful, there is no proper method of collection and elimination of data. There may also be noisy and erroneous data [7] as well as missing data, which may cause the inaccurate determination of flight position. Thus, reliability and usefulness of ADSB technology is still remains a questionable issue. Therefore, the aim of this project is to improve the accuracy aspect of the ADSB. A computing programme is developed by incorporating algorithms to eliminate erroneous signals and fill in the missing data. The developed computing programme is integrated into the ADS-B receiver to get a more accurate positioning and trajectory of the aircrafts.Due to the lack of ground tools to measure the usefulness of the results, the filtered trajectory will be plotted against the initial trajectory. Visual observation and comparison is made to valide the results. Stratux ADS-B receiver is used to collect data of the aircrafts for this project.